Neck involvement and disease recurrence in adenoid cystic carcinoma of the minor salivary glands: the role of surgery in primary and progressive disease. Issue 4 (April 2021) - Moratin, J.; Ledermann, A.; Schulz, A.D.; Metzger, K.; Ristow, O.; Hofele, C.; Engel, M.; Hoffmann, J.; Freier, K.; Lang, K.; Adeberg, S.; Horn, D.; et al.
Abstract: The aim of this study was to analyse the rates of metastatic events and clinical outcomes of patients with adenoid cystic carcinoma (ACC) of the minor salivary glands and to critically evaluate the role of surgical therapy. A retrospective cohort study was designed including all patients with ACC of the oral minor salivary glands treated in the study department during the years 2010–2017. Relevant clinicopathological data were analysed to determine factors with an impact on overall survival (OS) and progression-free survival (PFS). Forty-one patients with primary ACC of the oral cavity and the oropharynx were included. Cervical metastases were found in 14 patients (34.1%) and were shown to have a significant negative impact on OS ( P = 0.009) and PFS ( P = 0.03). Sixteen patients developed disease recurrence during follow-up (39.0%) and most patients exhibited local disease recurrence with or without regional or distant metastases (14/16, 87.5%). Local recurrence was treated successfully with surgery in five cases. We recommend surgical therapy for patients with ACC of the minor salivary glands, including elective neck dissection and microvascular reconstruction, to optimize the planning of adjuvant therapy.